2021
DOI: 10.1007/s00266-021-02232-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Scars with Laser-Assisted Delivery of Growth Factors and Vitamin C: A Comparative, Randomised, Double-blind, Early Clinical Trial

Abstract: Background: Scarring can jeopardize the final result of plastic surgeries. Deep dermal injuries activate dermal fibroblasts that produce excessive amount of collagen and 2 inflammatory cytokines and growth factors, which contributes to increased fibrous tissue and scarring tissue formation. Objectives:The aim of this double-blind, prospective, randomised clinical trial was to investigate the use of laser-assisted drug delivery (LADD) for scar improvement to support the establishment of LADD as standard therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Recently, several publications have specified the use of LADD with vitamins to treat skin disorders. Vitamin C or vitamin C plus growth factors GFs was the predominant focus of a small-sample study conducted by Machado et al (Machado et al, 2021b). The individuals in the group that was treated with vitamin C and GFs showed significantly reduced skin roughness compared to those treated with vitamin C alone.…”
Section: Data Extractionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, several publications have specified the use of LADD with vitamins to treat skin disorders. Vitamin C or vitamin C plus growth factors GFs was the predominant focus of a small-sample study conducted by Machado et al (Machado et al, 2021b). The individuals in the group that was treated with vitamin C and GFs showed significantly reduced skin roughness compared to those treated with vitamin C alone.…”
Section: Data Extractionmentioning
confidence: 99%
“…The individuals in the group that was treated with vitamin C and GFs showed significantly reduced skin roughness compared to those treated with vitamin C alone. Moreover, Mann-Whitney tests were conducted to compare the performances of two groups in studies (Machado et al, 2021a;Machado et al, 2021b). While these studies indicated satisfactory results, the interquartile range (IQR) and median results of the two studies varied.…”
Section: Data Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scars can be faded or removed, using a variety of techniques, including corticosteroid injections [ 2 ], cryotherapy [ 3 ], and laser therapy [ 4 ]. Identifying and evaluating scar tissue is the most crucial step in determining the extent of tissue damage and planning a suitable treatment pathway for scar management and removal [ 5 ]. However, determining and analyzing the scar regions in the skin tissue remains challenging.…”
Section: Introductionmentioning
confidence: 99%